Antimicrobial Activity of Extracellular Proteins Secreted by Bacillus subtilis ATCC21332 after being Induced with Cymbopogon flexuosus Essential Oil and Cultured in Different Growth Conditions - Nabilah Ahmad Alhadi; Hairul Shahril Muhamad; Salina Mat Radzi; Hanina Mohd Noor; Maryam Mohamed Rehan (Maxwell Scientific Publications, 2024)
Extracellular proteins secreted by diverse bacteria with broad spectrum of antimicrobial activity can be used as an alternative treatment against antibiotic resistant and spoilage microorganisms. However, the extracellular proteins produced by bacteria are affected by environmental stress factors and growth conditions. Therefore, antimicrobial activity of extracellular proteins secreted by Bacillus subtilis ATCC21332 in the presence of Cymbopogon flexuosus as stress inducer and cultivated in different growth conditions was evaluated against four selected strains of Gram-positive and Gram-negative bacteria, including Bacillus cereus, Escherichia coli, Shigella sonnei and Staphylococcus epidermidis by agar-well diffusion test and microdilution assay. Agar-well diffusion test was carried out to identify the antimicrobial susceptibility, while microdilution assay was done to determine the inhibition and bactericidal effects. B. subtilis ATCC21332 cells were treated with a low concentration (0.01 MIC) of C. flexuosus essential oil and cultured in various growth conditions such as different pH media (pH 6, pH 7 and pH 8) ornutrient sources, including 1% (w/w) of carbon (glucose, sucrose and starch), 1% (w/w) of nitrogen (casein, gelatin and urea) and 1% (w/w) of inorganic salt (sodium nitrate, calcium chloride and sodium dihydrogen phosphate). After 72 h of fermentation at 30°C, the secreted extracellular proteins were then extracted and analysed for antimicrobial activity. Results showed that the extracellular proteins secreted by stress induced B. subtilis ATCC21332 and cultivated in media with 1% of sucrose exhibited antimicrobial activity against two bacterial strains which are S. epidermidis and B. cereus with 8.0 ± 0.8 mm and 6.0 ± 0.0 mm of inhibition zone respectively. Meanwhile, the extracellular proteins extracted from bacteria cultured in each different media supplemented either with 1% of casein, 1 % of sodium nitrate and 1% of calcium chloride only showed antimicrobial activity against B. cereus with inhibition zone of 7.5 ± 0.5 mm, 8.0 ± 1.0 mm and 9.0 ± 0.0 mm respectively. Although the extracellular proteins indicated inhibitory effect against B. cereus and S. epidermidis, however the proteins only exhibited bactericidal effect towards B. cereus.